2013
DOI: 10.1111/jonm.12055
|View full text |Cite
|
Sign up to set email alerts
|

Does value congruence between nurses and supervisors effect job satisfaction and turnover?

Abstract: Nurse Administrators can use these results to develop policies to address the turnover especially in the area of leadership support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 37 publications
2
29
0
2
Order By: Relevance
“…One study in the USA also found that a lack of P-O fit can lead to decreased job satisfaction and increased turnover intention 12. One study on nurses' P-O fit found that congruence on leadership practice was directly related to job satisfaction, and congruence on leadership support was inversely related to turnover intention 10. In Kristof's meta-analysis, results suggested that the effect of P-O fit from the needs-supplies dimension on job satisfaction was around 0.37,4 compared to which our result was lower (0.244).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study in the USA also found that a lack of P-O fit can lead to decreased job satisfaction and increased turnover intention 12. One study on nurses' P-O fit found that congruence on leadership practice was directly related to job satisfaction, and congruence on leadership support was inversely related to turnover intention 10. In Kristof's meta-analysis, results suggested that the effect of P-O fit from the needs-supplies dimension on job satisfaction was around 0.37,4 compared to which our result was lower (0.244).…”
Section: Discussionmentioning
confidence: 99%
“…One study on nurses found that value congruence influenced job satisfaction and their attitude towards wards 9. Another study was about nurses-supervisor value congruence, which is only a part of P-O fit 10. Until now, P-O fit of needs-supplies dimension and its relationship with job satisfaction and turnover intention have not been fully tested in the area of human resources for health.…”
Section: Introductionmentioning
confidence: 99%
“…) and contextual resources, e.g. supportive leadership (Hunt , Lu & Guy ). Such a salutary perspective has its foundations in stress buffer theory, proposing that stressors do not inevitably harm an employee's well‐being and health if an individual has certain buffering resources as coping assets (Cohen & Wills ).…”
Section: Introductionmentioning
confidence: 99%
“…These coping resources include various individual factors such as appropriate emotion regulation strategies (Gross 1998a,b, Bechtoldt et al 2011, Schreurs et al 2014, Yoo & Arnold 2014, Zapf et al 2014) and contextual resources, e.g. supportive leadership (Hunt 2014, Lu & Guy 2014. Such a salutary perspective has its foundations in stress buffer theory, proposing that stressors do not inevitably harm an employee's well-being and health if an individual has certain buffering resources as coping assets (Cohen & Wills 1985).…”
Section: Introductionmentioning
confidence: 99%
“…, Rodwell et al . , Hunt ).Yet, studies that assess the impact of support received from administration or management as a result of the abuse on the intent to leave the profession are lacking; and no similar study has been conducted in Lebanon. As turnover is preceded by intention to leave, it was postulated in this study that administrative/managerial support will negate the effects of abuse.…”
Section: Introductionmentioning
confidence: 99%